Electrical theory for renewable energy - Goodstal, Gary (Delmar, 2013)
Essential for anyone interested in a career in renewable energy, ELECTRICAL THEORY FOR RENEWABLE ENERGY presents a solid foundation of electrical theory and applications for both photovoltaic (PV) power and wind power in one engaging book. Designed to apply to electricians as well as individuals specializing in PV and wind turbines, each chapter provides a common technical language and knowledge base for all renewable energy practitioners so that all members of the team (i.e., practitioners, designers, installers and engineers) are able to work together effectively in the field. With multiple examples and opportunities for practice, this book covers the basic electrical theory that is required for you to understand any renewable energy source that generates electricity.